2013
DOI: 10.1021/jp311049f
|View full text |Cite
|
Sign up to set email alerts
|

Neighboring Effect in Fragmentation Pathways of Cage Guanylhydrazones in the Gas Phase

Abstract: ESI-MS/MS investigation of the mono- and bis(guanylhydrazone) derivatives 1-5 based on adamantane and pentacycloundecane (PCU) skeleton was described. Elimination of neutral guanidine is the most abundant reaction channel in the case of 2,4-adamantyl and PCU derivatives 4 and 5, while the elimination of CH2N2 fragment is preferred for other compounds. This was attributed to the cage opening of adamantane or PCU skeletons in the former case leading to the formation of the cyclohexyl- or cyclopropylcarbinyl carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Tautomerism of the molecular ion [A1] 2+ → [A2] 2+ ( m / z 190) appears to be a prerequisite for ammonia loss and formation of the fragment ion [A3] 2+ ( m / z 181). A similar tautomerism is reported by Šekutor et al ., where the authors showed that one of the three fragmentation pathways of adamantyl guanylhydrazones includes the tautomeric shift of a proton from one of the nitrogen atoms to another in a singly protonated molecule of guanylhidrazone. DFT calculations showed that the activation energy for this process is 47.8 kcal mol −1 , whereas the energy difference between the two tautomers was 33.8 kcal mol −1 .…”
Section: Resultssupporting
confidence: 84%
“…Tautomerism of the molecular ion [A1] 2+ → [A2] 2+ ( m / z 190) appears to be a prerequisite for ammonia loss and formation of the fragment ion [A3] 2+ ( m / z 181). A similar tautomerism is reported by Šekutor et al ., where the authors showed that one of the three fragmentation pathways of adamantyl guanylhydrazones includes the tautomeric shift of a proton from one of the nitrogen atoms to another in a singly protonated molecule of guanylhidrazone. DFT calculations showed that the activation energy for this process is 47.8 kcal mol −1 , whereas the energy difference between the two tautomers was 33.8 kcal mol −1 .…”
Section: Resultssupporting
confidence: 84%
“…3 This further encouraged us to undertake a systematic study of this type of compounds, covering various aspects of their nature and properties. [4][5][6][7][8] The most facile way to synthesize adamantyl guanylhydrazones was to use the corresponding adamantyl ketones as a key starting material. On the other hand, in order to prepare adamantyl aminoguanidines we used the corresponding adamantyl amines (Scheme 1).…”
Section: Syn Lettmentioning
confidence: 99%
“…The studies we conducted included a structural characterization of all the possible compound geometries using a computational approach, [4][5][6] fragmentation studies in the gas phase, 4 oxo-anion binding studies, 7 enzyme-inhibition testing, 8 and their incorporation into the liposomes. 5 We calculated the enthalpies for compounds 1-12 and for all of their isomers using B3LYP/6-311+G (d,p) level of theory.…”
Section: Syn Lettmentioning
confidence: 99%
See 2 more Smart Citations